Biogas untuk Menghasilkan Energi Listrik - Paniran; rosmaliati; Abdul Natsir (DIELEKTRIKA, 2023)
Biogas is a methane gas produced from the fermentation of organic matter by anaerobic bacteria. Utilization of biogas as an energy source can be done by burning biogas directly, and indirectly by converting it into electrical energy. Biogas-fueled electric energy potential to be developed in the NTB area. The fundamental reason is: the government program "Earth One Million Cows" which is supposed to happen in 2013, rising prices of petroleum fuel and the scarcity of inorganic fertilizers. To realize the above research activities, will do the following steps: 1) Development of fixed-dome digester with a size of 8 m3, 2) the charging of organic materials in the digester to produce biogas, 3) perform gas reservoirs in the media that has been prepared, 4) integrate system are made, 5) test and measurement under load conditions. Test results on Biogas Power Plant in the laboratory EBT of the Engineering Faculty of Mataram Universit, with 8m3 digester produces biogas production at the effective time of 2.152 m3/day. Consumption of biogas to the generator at 200watt load is 0.133 m3 / 15, or the conversion of biogas into electricity coefficient is 2.4 m3/kwh. Production of biogas a day if converted to a 200Watt power burden to last about 4 hours.